The Effect Of Aromatherapy Massage on Anxiety Levels in Postpartum Women - Erinda Nur Pratiwi; Siti Nurjanah; Ajeng Maharani Pratiwi; Aris Prastyoningsih; Atiek Murharyati; Hanugrah Ardya Crisdian Saraswati (Journal of Midwifery, 2020)
Anxiety is an affective disorder characterized by deep and ongoing feelings of fear or worry. Research in Germany found 16.2% of 6-week postpartum mothers with pure anxiety disorder control (phobias, panic, acute adjustment disorder with anxiety). On the first day of the postpartum period, 82% were diagnosed with phobias. Miller et al showed that 10% of women experienced symptoms of anxiety and controls from 6 weeks to 6 months after delivery. Aromatherapy is a non-pharmacological strategy for anxiety management developed to reduce anxiety in patients. Aromatherapy can be used as an emotional therapy, thereby enhancing relaxation. Besides aromatherapy, aromatherapy massage can be used for stress management for individual health, and has often been used as a therapy to control pain and reduce psychological stress, such as anxiety. The results of a study conducted by Winai in 2003 explained that jasmine oil has a stimulating effect on nervous system function, by inhaling jasmine oil it can affect brain wave activity, increase positive emotions including feelings of happiness, prosperity, activity, freshness and romance and improve mood. The mood or mood that is often erratic in postpartum mothers can get better by inhaling jasmine oil. One of the types of complementary therapy according to Permenkes Number 15 of 2018 is aromatherapy, which is a popular therapy for mothers and midwives. The purpose of this study was to determine the effect of aromatherapy massage on anxiety levels in postpartum mothers. The benefit of this research is that it can be a complementary therapy, especially for postpartum mothers who experience anxiety so that they are comfortable living as a new mother in their life. The research design used a Quasi Experimental design, which is a study that does not have strict restrictions on randomization with the Non-Randomized Control Group Pretest and Posttest Design, the grouping of samples in the treatment group and the control group is not done randomly.